Selenium Enhances the Growth of Bovine Endometrial Stromal Cells by PI3K/AKT/GSK-3β and Wnt/β-Catenin Pathways - Junsheng Dong; Zi Wang; Fan Fei; Yeqi Jiang; Yongshuai Jiang; Long Guo; Kangjun Liu; Luying Cui; Xia Meng; Jianji Li; Heng Wang (Veterinary Sciences)
The bovine uterus is susceptible to bacterial infections after calving, particularly from Escherichia coli (E. coli), which often results in endometritis. Additionally, postpartum stress in cows can elevate cortisol levels in the body, inhibiting endometrial regeneration and reducing immune function, thereby further increasing the risk of infection. Selenium (Se) is a common feed additive in dairy farming, known for its anti-inflammatory and antioxidant effects. The aim of this study was to investigate the regulatory role of Se in the growth of bovine endometrial stromal cells (BESCs) under the conditions of LPS-induced inflammatory damage at high cortisol levels. BESCs were treated with 1, 2, 4 μM Se in combination with co-treatment of LPS and cortisol. The results indicated that LPS inhibited the cell viability and reduced the mRNA expression of CTGF, TGF-β1, and TGF-β3. Additionally, LPS increased apoptosis, hindered the cell cycle progression by blocking it in the G0/G1 phase, and suppressed the PI3K/AKT/GSK-3β and Wnt/β-catenin signaling pathways. Furthermore, increased concentrations of cortisol can exacerbate the impacts of LPS on cell proliferation and apoptosis. Conversely, the supplementation of Se promoted cell viability, increased the mRNA expression of TGF-β1 and TGF-β3, and enhanced cell cycle progression, while simultaneously repressing cell apoptosis as well as activating the PI3K/AKT/GSK-3β and Wnt/β-catenin signaling pathways. The above findings demonstrated that Se can promote cell proliferation, reduce cell apoptosis, and aid in the growth of BESCs damaged by LPS under high levels of cortisol. The potential mechanisms may be associated with the regulation of the PI3K/AKT/GSK-3β and Wnt/β-catenin signaling pathways.